Hardware development of ultrasonics tomography for composition determination of water and oil flow - Abdul Rahim, Ruzairi; Ng, Wei Nyap; Fazalul Rahiman, Mohd. Hafiz (International Frequency Sensors Association (IFSA), 2007)
A monitoring system for water and oil flow using ultrasonic Tomography is implemented. Information such as the type of flow, the composition of the water and oil can be obtained from the system. The composition of the flow is determined based on the propagation time of the ultrasonic waves. The ultrasonic Tomography system includes the sensors fixture design, signal conditioning circuits and image reconstruction software. The image reconstruction algorithm that used is the Linear Back Projection (LBP) algorithm.